Comparison of 24 Hour Urinary Protein and Spot Urinary Protein- Creatinine Ratio in the Assessment of Proteinuria in Patients with Glomerulonephritis - Ahmed, Parvez Iftekhar; Islam, Md Nazrul; Alam, Md Babrul; Bhuiya, Ferdous Kamal; Noman, Mesbah Uddin; Chowdhury, Md Nizamuddin (Journal of Dhaka Medical College, 2015)
Context: Glomerulonephritis is an important cause of morbidity and mortality among all age group in Bangladesh. This cross sectional study was carried out with an aim to observe the comparison of 24 hour urinary protein and spot urinary protein- creatinine ratio in patients with glomerulonephritis in 3 group: on basis of 24 hour total protein, GFR level and serum albumin level. Methods: A total number of 128 consecutive patients having glomerulonephritis with 18 to 70 years who came in the Nephrology Unit, Dhaka Medical College Hospital, Dhaka, during the period of January to December of 2011 were included in this study. Patients with proteinuria other than glomerulonephritis like DM, UTI and Hypertension and <18 years of age were excluded from the study. Results: A significant positive correlation was found between 24 hour Urine Protein with Protein Creatinine Ratio on the patients having 24 hour Urinary protein <0.2 gm, 0.2-<1 gm, 1- 3.4 gm and 3.5-6 gm respectively. No correlation was found between 24 hr Urine Protein with Protein Creatinine Ratio on the patients having 24 hour Urinary protein >6 gm. A significant positive correlation was also found between 24 hour Urine Protein (gm/24 hour) with Protein Creatinine Ratio, which were in patients having GFR <15 ml/min/1.73m2 body surface area, 15-29 ml/min/1.73m2 body surface area, 30-59 ml/min/1.73m2 body surface area, 60-89 ml/ min/1.73m2 body surface area and e90 ml/min/1.73m2 body surface area respectively. However, the result of the group having GFR <15 ml/min/1.73m2 body surface was positively correlated but not very convincing. In this present series it was observed that a significant positive correlation was found between 24 hr Urine Protein (gm/24 hour) with Spot Urinary Protein Creatinine Ratio in relation to serum albumin level; r=0.658; (p<0.001) and r=0.707; (p<0.001) in patients having serum albumin level >30gm/dl and 20-30 gm/dl respectively. But because of only one sample in the group having <20 gm/dl serum albumin, no comparison could be carried out. Conclusion: P/C ratio provided a very useful, simple and convenient method for quantitative assessment of protein and can replace 24 hour urine collection method in indoor, outpatients and in follow up clinics as it gives quick and reliable results and avoids the inconvenience and short comings associated with 24 hour urine collection. J Dhaka Medical College, Vol. 23, No.2, October, 2014, Page 194-202